Tourism data collection. An analysis at subnational level in Iceland - Lilja Berglind Rögnvaldsdóttir 1975- (2015)
The rising importance of tourism in the Icelandic economy calls for a thorough and systematic assembling of tourism statistics in order to regulate and organise the industry. Common language and international definitions are indispensable in this matter. The World Tourism Organization has published international guidelines and recommendations for tourism statistics which is important for each country to follow as international definitions and methods permit countries to measure and understand the scope of the industry at each place, enabling global comparison. The aim of this article is to map up the obtainable tourism data sources in Iceland according to the framework of UNWTO Compendium of Tourism Statistics 2014, and means of linking these to the regional level. This is accomplished through compiling and analysing data produced within Statistics Iceland as well as from other sources. The results show a lack of data at the regional level. The sole systematic data collection by regions is the accommodation statistics by Statistics Iceland. Visitor numbers are not counted on a sub-national level and very few regional statistics can be retrieved from the ITB inbound visitor survey. This lack of data makes statistical analysis of tourism at the regional level in Iceland difficult and expensive.